Karakteristik Akad Mudharabah Pada Transaksi Penyimpanan Dana Nasabah di Bank Syariah - Siti Nur Shoimah; Dyah Ochtorina Susanti; Rahmadi Indra Tektona (Jurnal Risalah Hukum, 2020)
Many people assume that mudharabah savings in Islamic banks are the same as deposits in conventional banks. In contrast, mudharabah savings have their characteristics, one of which is adopting a revenue-sharing system in managing customer deposit funds. In this study, researchers used a normative method with a statutory approach and conceptual approach. The results of this study are the discovery of mudharabah contract characteristics in depositing customer funds in Islamic banks which can be seen from 6 things, namely investment deposits, legal subjects or parties, profit sharing, business risk distribution, guarantees, and fund withdrawals by the Customer. Keywords: Mudharabah Agreement; Depositing Customer Funds; Islamic